ANALISIS KINERJA SUPPLY CHAIN DENGAN METODE SUPPLY CHAIN OPERATION REFERENCE (SCOR) DAN ANALYTICAL HIERARCHY PROCESS (AHP) PADA PT X - Zachvier Adhari Brizadly (2023)
PT X is a raw material supplier company for several Food & Beverage companies in the Jakarta area. However, PT X often experiences stock shortages to supply raw materials when there is fluctuating demand. If this continues, it will certainly affect the performance of PT X and will lose competition with competitors to fulfill the needs of PT Y. Therefore, a method that can analyze the company's overall performance is needed, requiring a more comprehensive, systematic, and well-integrated SCM performance evaluation framework. This research uses the Supply Chain Operation Reference (SCOR) method which is considered more comprehensive, systematic, and integrated. Based on the measurement results, it can be concluded that from the 20 supply chain indicators at the selected PT X, the total supply chain performance value is 64.987, which means that the supply chain performance at PT X is in the average category. Including each performance value for the core processes in the level 1 matrix, namely 13.098 in the plan matrix, 2.789 in the source matrix, 44.568 in the make matrix, 2.279 in the deliver matrix, and 2.252 in the return matrix.